From FORM OF THE CONCERN TO RESIST COVID-19 THROUGH THE DISTRIBUTION OF 5,000 MASKS AND HAND SANITIZERS TO THE SOCIETY IN TRADISIONAL MARKET PUNI RUTENG - MANGGARAI - Petrus Sii; Priska Filomena Iku; Yuvantinus Effrem Warung; Angela Klaudia Danu; Antonius Nesi (Randang Tana - Jurnal Pengabdian Masyarakat, 2020)
This article is motivated by the increasing of covid-19's cases in Indonesia in general and the concern to society of Manggarai who are not wearing masks when they are outside the home, especially in public places such as markets, terminals, and shopping areas. The distribution of the masks for free also depends on the limitations of masks in the markets, and if there is still some stock, they are cost higher than normal prices. The distribution of those masks for free is done to build public awareness to overcome covid-19. This activity was on May 7, 2020 at Puni traditional market of Ruteng. The target of this activity were all people living around Puni Ruteng. The method used is the distribution of masks for free to all levels of the society, while hand sanitizer only distributed to the driver of public transportations which often did direct contact with the passengers every day. In addition to that, the team of PKM gives some explanation about how to wash hands by using hand sanitizer for health, how to wear a mask and the duration of time wearing masks. In this activity, each person has received 2 pieces of masks given by PKM's team so they can be replaced every day. The result of this activity can increase people's awareness of the importance of maintaining health, and tackling the spread of covid-19 in the district of Manggarai in general